Urgensi Fatwa dan Sidang Isbat dalam Penentuan Awal Bulan Kamariah di Indonesia: The Urgency of Fatwa and Isbat Assemblies in Determining the Beginning of the Month of Kamariah in Indonesia - Qulub, Siti Tatmainul; Munif, Ahmad (Jurnal Bimas Islam, 2023)
This study examines the urgency of fatwas and isbat hearings in determining the beginning of the month of Kamariah in Indonesia. MUI issued MUI Fatwa in 1981 and MUI Fatwa No. 2 of 2004, which contains the initial determination of Ramadan, Shawwal, and Dhul-Hijjah, where all Muslims in Indonesia are obliged to obey Government decrees carried out through isbat sessions. However, many still need to obey the provisions of the Government. This research answers two formulations of the problem. First, what is the urgency of the MUI Fatwa and Isbat Council in determining the beginning of the month of Kamariah in Indonesia? Second, how much did the MUI Fatwa and Isbat Council contribute to unifying the beginning of the month of Kamariah in Indonesia? The descriptive-analytical method with a fiqh Falak approach answers both problem formulations. The study yielded two findings. First, the urgency of the MUI Fatwa and the Isbat Assembly is a form of the responsibility of scholars and the Government to the Indonesian people to create togetherness, provide certainty of opinion, and minimize differences and conflicts. Second, the MUI Fatwa is a step and initial foothold for the Government to set criteria for the beginning of the month of Kamariah (MABIMS and Neo MABIMS). The Isbat Assembly became a forum for collecting various information, both the results of hisab and reports. Both contribute to efforts to realize the benefits of togetherness during worship.